Reloading Data Protection
XV, 369 p. 13 illus., 5 illus. in color.
Keywords: This volume brings together papers that offer conceptual analyses, highlight issues, propose solutions, and discuss practices regarding privacy and data protection. The first section of the book provides an overview of developments in data protection in different parts of the world. The second section focuses on one of the most captivating innovations of the data protection package: how to forget, and the right to be forgotten in a digital world. The third section presents studies on a recurring, and still important and much disputed, theme of the Computers, Privacy and Data Protection (CPDP) conferences : the surveillance, control and steering of individuals and groups of people and the increasing number of performing tools (data mining, profiling, convergence) to achieve those objectives. This part is illustrated by examples from the domain of law enforcement and smart surveillance. The book concludes with five chapters that advance our understanding of the changing nature of privacy (concerns) and data protection.